Improving The Knowledge of School Health Ambassador (Dokter Kecil) Through "Dinos" Program For Elementary School Students In The Catchment Area of Puskesmas Seberang Padang - Semiarty, Rima; Yetti, Husna; Rahmaddiansyah, Refa; Muhammad Helmi, Iqbal; Zulen, Ilham Andhika; Kurnia, Nurul Syifa; Maya Amanda; Salsabilla Dhiyaa Syifa; Athiyyah, Salsa Naudzul; Laila Nur Azizah (Jurnal Pengabdian Pada Masyarakat METHABDI, 2024)
Health education within schools plays a crucial role in enhancing children's health and establishing a safe and healthy learning environment. Despite this, the risk of illness in schools remains a concern, particularly for elementary school-aged children who are susceptible to sanitation-related health issues. The “Dokter Kecil” (or School Health Ambassador) program is designed to engage students in promoting the health of individuals, families, and their surroundings. This research aims to reintroduce the program in the Puskesmas Seberang Padang area, focusing on a promotive and preventive approach known as DINOS. The program's effectiveness was evaluated using pre-test and post-test questionnaires to assess the knowledge of the student participants. Based on the normality test of pretest and post-test score data using statistical tests, it is found that the Sig value (2-tailed) is 0.002 < 0.05. Therefore, it can be concluded that there is a significant difference between the results of the DINOS material exposure and simulation on pre-test and post-test data. Data analysis revealed a significant difference between the pre-test and post-test results, indicating the effectiveness of the material presentation and DINOS simulation. These results are expected to help better school health program implementation and more successfully address health issues for Indonesian school-age children, especially in the Puskesmas Seberang Padang area.